Ländliche Neusiedlung im Gebiet des heutigen Österreich vom Ende des 19. Jahrhunderts bis zur Gegenwart - Penz, Hugo (ERDKUNDE, 1986)
In Austria the preconditions for new farms have been unfavourable: only, in Burgenland, which came into Austrian possession in1921, was extensive landed property important. It was possible to create new settlements through the cultivation of wasteland, but only with difficulty. In any case such expansion had little political support. The farmers’ union, which has determined Austrian agrarian policy since 1918, has always been opposed to the opening of new farms. Before 1914 the Austrian state supported no new farms. After the First World War an agrarian reform was de manded, but in 1919 the parliament only decided on the Wiederbesiedlungsgesetz, by which farms, that had been bought by large landowners between 1870 and 1914, were to be bought back into the possession of farmers again. The success of this action was very modest. Until 1928 only 488 farms, for the most part rented, were resettled. Even after1930 there was no organization for new farms. The Austrian government supported only a few activities with subsidies. Apart from suburban settlements around Vienna and some farm workers’ settlements, 28 small farms were created by the division of extensive landed property in Burgenland. The colonization of moorland (3 farms) played a minor role. The re-colonization of second farmsteads on the upper limit of permanent settlements in Salzburg was, however, more important. During the National Socialist period (1938-1945), when Austria was part of the German empire, new settlements also remained unimportant (192 new farms). After 1945 no agrarian reform was implemented in Austria. The re-colonization of second farmsteads in the province of Salzburg was the most important. Today new settlements in rural areas are insignificant. In fact, since 1972, the Ministry of Agriculture has not provided any subsidies for such activities.